Revisiting the taxonomy of Exacum courtallense (Gentianaceae) and recognizing E. courtallense var. laxiflorum at the species rank - Geethakumary, M.p.; Deepu, S.; Kissling, J.; Pandurangan, A.g. (Phytotaxa, 2022)
Morphological, phenological and ecological evidences support the exclusion of Exacum courtallense var. laxiflorum Gamble (synonym: E. courtallense var. bonaccordense M. Mohanan) from E. courtallense Arn. resulting in the establishment of a new species Exacum laxiflorum (Gamble) Geethakumary, Deepu, Kissling & Pandurangan.